Effect of partial crystallization on the mechanical properties and cytotoxicity of bioactive glass from the 3CaO center dot P2O5-SiO2-MgO system - Daguano, J. K. M. E.; Strecker, K.; Ziemath, E. C. [UNESP]; Rogero, S. O.; Fernandes, M. H. V.; Santos, C. (Elsevier B.V., 2012)
The aim of this study is to report on the development and characterization of bioactive glass and glass-ceramics from the 3CaO center dot P2O5-SiO2-MgO-system, using different degrees of cristallinity for applications as an implant material. A methodology was proposed to induce crystallization of phases. Bioglass samples of the nominal composition (wt %) 57.75 CaO center dot P2O5-30 SiO2-17.25 MgO were heat treated at temperatures ranging from 700 to 1100 degrees C for 4 h. The findings from the research illustrate how partial crystallization and phase transformations modified the microstructure of the based glassy material, resulting in improved mechanical properties. The maximum gain was measured for samples treated at 975 degrees C, having a hardness of 6.2 GPa, an indentation fracture toughness of 1.7 MPam(1/2) and a bending strength of 120 MPa, representing an increase of 30, 55 and 70%, respectively, when compared to the nucleated glass. The highest elastic modulus of about 130 GPa was determined for samples treated at 1100 degrees C. As a preliminary biological evaluation, "in vitro" cytotoxicity tests were realized to determine the cytotoxic level of the materials, using the neutral red uptake method with NCTC clones L929 from the American Type Culture Collection (ATCC) bank. on the other hand, no significant influence of the partial crystallization on cytotoncity was observed. The results provide support for implant materials based on the 3CaO center dot P2O5-SiO2-MgO-system. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Glass-ceramics; Crystallization; Microstructure; Mechanical properties; Cytotoxicity